The Influence of Safarwadi Pamijahan Religious Tourism on the Improvement of the Economy of Pamijahan MSMEs - Maspupah, Ima; Sandi, Kurniawan; Nurdin, Ikhsan (Ta'amul: Journal of Islamic Economics, 2025)
This study is motivated by the rapid growth of the tourism sector in Indonesia, particularly religious tourism, which plays a vital role in driving local economic development. In Kampung Pamijahan, Tasikmalaya Regency, religious tourism—centered around the tomb of Sheikh Abdul Muhyi—has attracted a significant influx of visitors. This phenomenon has created economic opportunities for local micro, small, and medium enterprises (MSMEs), notably kolang-kaling traders, whose products represent a regional specialty. The objective of this research is to analyze the influence of Safarwadi Pamijahan religious tourism on the economic improvement of these traders. A quantitative approach was employed using a descriptive analysis method. The study utilized a saturated sample of 40 respondents, representing the entire population of kolang-kaling traders in the area. Data collection was conducted through a field research approach with structured instruments, while hypothesis testing was performed using the t-test. Findings reveal that religious tourism significantly influences MSME economic performance, indicated by a significance value of 0.004 (<0.05) and a t-count of 3.033 (>1.686). The coefficient of determination shows that tourism contributes 19.5% to traders’ economic growth, while 80.5% is affected by other external factors. These results confirm that Safarwadi Pamijahan religious tourism serves as an essential but not exclusive driver of local MSME development. The contribution of this study lies in providing empirical evidence of the partial role of religious tourism in enhancing community-based economies, which can inform regional tourism and economic policies.